Exhaust gas recirculation method for motor vehicle internal combustion engine, has exhaust recirculation flow control dependent on mass airflow to inlet of engine - FONTVIEILLE LAURENT (2003)
The exhaust gas recirculation method for a motor vehicle internal combustion engine uses a valve (28) for regulation of the return gas flow to the intake (18). The method involves calculating the value of a valve control signal as a function of the quantity of fuel injected and a variable using the quantity of air circulating in the engine. The control signal for the valve is modified depending on the mass airflow (Q) in the inlet (18) of the engine. Pour la commande d'une soupape (28) de régulation d'un flux de gaz d'échappement recirculés dans le collecteur d'admission (18) d'un moteur à combustion interne équipé d'un circuit de recirculation des gaz d'échappement, on calcule la valeur (C) d'une consigne de commande de la soupape en fonction de la quantité de carburant injectée dans le moteur et d'une variable représentative de la quantité d'air circulant dans le moteur, et l'on pilote la soupape (28) en fonction de la valeur de la consigne.La consigne de commande de la soupape est élaborée à partir du débit d'air massique dans le collecteur d'admission du moteur.